Business process management centre of excellence as a source of knowledge - Bitkowska, Agnieszka (Business, Management and Economics Engineering, 2018)
The aim of this article is to present the functioning of the Business Process Management Centre of Excellence (BPM CoE) from a knowledge perspective. Empirical research has been carried out in an enterprise operating on the territory of Poland in 2017. The results revealed that enterprises with the implementation of process approach tend to maximize knowledge diffusion and develop organizational competencies via organizing Business Process Management Centre of Excellence in the world and in Poland. An increasing number of companies adopting a Business Process Management Centre of Excellence, which is a centre for process improvement and provides many good practical solutions.